The Rosenzweig-Porter model revisited for the three Wigner-Dyson symmetry classes - Čadež, Tilen; Kumar Nandy, Dillip; Rosa, Dario [UNESP]; Andreanov, Alexei; Dietz, Barbara (IOP Publishing, 2024)
Interest in the Rosenzweig-Porter model, a parameter-dependent random-matrix model which interpolates between Poisson and Wigner-Dyson (WD) statistics describing the fluctuation properties of the eigenstates of typical quantum systems with regular and chaotic classical dynamics, respectively, has come up again in recent years in the field of many-body quantum chaos. The reason is that the model exhibits parameter ranges in which the eigenvectors are Anderson-localized, non-ergodic (fractal) and ergodic extended, respectively. The central question is how these phases and their transitions can be distinguished through properties of the eigenvalues and eigenvectors. We present numerical results for all symmetry classes of Dyson’s threefold way. We analyzed the fluctuation properties in the eigenvalue spectra, and compared them with existing and new analytical results. Based on these results we propose characteristics of the short- and long-range correlations as measures to explore the transition from Poisson to WD statistics. Furthermore, we performed in-depth studies of the properties of the eigenvectors in terms of the fractal dimensions, the Kullback-Leibler (KL) divergences and the fidelity susceptibility. The ergodic and Anderson transitions take place at the same parameter values and a finite size scaling analysis of the KL divergences at the transitions yields the same critical exponents for all three WD classes, thus indicating superuniversality of these transitions.
Keywords: Anderson transition; ergodic transition; fractal states; non-ergodic phase; quantum Chaos; random matrix theory; Wigner-Dyson ensembles